PEMBERDAYAAN KELOMPOK NELAYAN WANASARI TUBAN MELALUI IMPLEMENTASI CSR PT. PERTAMINA (PERSERO) DPPU NGURAH RAI - Felanza, Merdi; Nugroho, Wahyu Budi; Kebayantini, Ni Luh Nyoman (JURNAL ILMIAH SOSIOLOGI (SOROT), 2017)
ABSTRACT Implementation of CSR (Corporate Social Responsibility) PT. Pertamina (Persero) have done through empowerment of Wanasari Fisherman Group, Tuban. The empowerment program is a cultivation of mangrove crabs and forest conservation in Integrated Ecotourism Wanasari. This research is using qualitative descriptive method to describe the flow of empowerment and influence of mangrove crab cultivation program through observation, interviews and secondary data analysis as a data collection method. Structural Functional and Community Empowerment theory has been used to analyze this research. The program uses the concept of bottom-up in implementation of community empowerment. The adaptation of empowerment starts from social mapping to explore the potential of local communities. The success mangrove crab cultivation gives effect to the new program in Integrated Ecotourism Wanasari Tuban, namely the mangrove forest education program, culinary tourism, art, culture and ecotourism. Keywords : Implementation of CSR PT. Pertamina (Persero) DPPU Ngurah Rai, Wanasari Fishermen Group, Mangrove Crab Cultivation